Euclid preparation: I. The Euclid wide survey - Scaramella, Roger A.; Amiaux, J.; Mellier, Y.; Burigana, C.; Carvalho, C. S.; Cuillandre, J.-C.; Silva, A. Da; Derosa, A.; Dinis, J.; Maiorano, E.; Maris, M.; Tereno, I.; et al. (Astronomy and astrophysics, 2022)
Euclid is a mission of the European Space Agency that is designed to constrain the properties of dark energy and gravity via weak gravitational lensing and galaxy clustering. It will carry out a wide area imaging and spectroscopy survey (the Euclid Wide Survey: EWS) in visible and near-infrared bands, covering approximately 15 000 deg2 of extragalactic sky in six years. The wide-field telescope and instruments are optimised for pristine point spread function and reduced stray light, producing very crisp images. This paper presents the building of the Euclid reference survey: the sequence of pointings of EWS, deep fields, and calibration fields, as well as spacecraft movements followed by Euclid as it operates in a step-and-stare mode from its orbit around the Lagrange point L2. Each EWS pointing has four dithered frames; we simulated the dither pattern at the pixel level to analyse the effective coverage. We used up-to-date models for the sky background to define the Euclid region-of-interest (RoI). The building of the reference survey is highly constrained from calibration cadences, spacecraft constraints, and background levels; synergies with ground-based coverage were also considered. Via purposely built software, we first generated a schedule for the calibrations and deep fields observations. On a second stage, the RoI was tiled and scheduled with EWS observations, using an algorithm optimised to prioritise the best sky areas, produce a compact coverage, and ensure thermal stability. The result is the optimised reference survey RSD_2021A, which fulfils all constraints and is a good proxy for the final solution. The current EWS covers ≈14 500 deg2. The limiting AB magnitudes (5σ point-like source) achieved in its footprint are estimated to be 26.2 (visible band IE) and 24.5 (for near infrared bands YE, JE, HE); for spectroscopy, the Hα line flux limit is 2 × 10−16 erg−1 cm−2 s−1 at 1600 nm; and for diffuse emission, the surface brightness limits are 29.8 (visible band) and 28.4 (near infrared bands) mag arcsec−2.
Gesehen am 23.08.2022